USP19 deubiquitinates EWS-FLI1 to regulate Ewing sarcoma growth - Maria E. Gierisch (Nature Portfolio, 2019)
Abstract Ewing sarcoma is the second most common pediatric bone and soft tissue tumor presenting with an aggressive behavior and prevalence to metastasize. The diagnostic translocation t(22;11)(q24;12) leads to expression of the chimeric oncoprotein EWS-FLI1 which is uniquely expressed in all tumor cells and maintains their survival. Constant EWS-FLI1 protein turnover is regulated by the ubiquitin proteasome system. Here, we now identified ubiquitin specific protease 19 (USP19) as a regulator of EWS-FLI1 stability using an siRNA based screening approach. Depletion of USP19 resulted in diminished EWS-FLI1 protein levels and, vice versa, upregulation of active USP19 stabilized the fusion protein. Importantly, stabilization appears to be specific for the fusion protein as it could not be observed neither for EWSR1 nor for FLI1 wild type proteins even though USP19 binds to the N-terminal EWS region to regulate deubiquitination of both EWS-FLI1 and EWSR1. Further, stable shUSP19 depletion resulted in decreased cell growth and diminished colony forming capacity in vitro, and significantly delayed tumor growth in vivo. Our findings not only provide novel insights into the importance of the N-terminal EWSR1 domain for regulation of fusion protein stability, but also indicate that inhibition of deubiquitinating enzyme(s) might constitute a novel therapeutic strategy in treatment of Ewing sarcoma.